The Agricultural College Editor and the Nitrite Scare: Reporting Utter Chaos - Fred Causley (Journal of Applied Communications, 1981)
The responsibility for cutting a path through the tangled wood of information and misinformation to lead excited consumers, pork producers, legislators and even some scientists to the facts of the nitrite issue lies squarely on the shoulders of editors - in both print and electronic media.